Population attributable fractions and joint effects of key risk factors for multiple sclerosis. (April 2016) - van der Mei, IAF; Lucas, RM; Taylor, BV; Valery, PC; Dwyer, T; Kilpatrick, TJ; Pender, MP; Williams, D; Chapman, C; Otahal, P; Ponsonby, A-L
Aim: We examined the combined effect of having multiple key risk factors and the interactions between the key risk factors of multiple sclerosis (MS). Methods: We performed an incident case-control study including cases with a first clinical diagnosis of central nervous system demyelination (FCD) and population-based controls. Results: Compared to those without any risk factors, those with one, two, three, and four or five risk factors had increased odds of being an FCD case of 2.12 (95% confidence interval (CI), 1.11–4.03), 4.31 (95% CI, 2.24–8.31), 7.96 (95% CI, 3.84–16.49), and 21.24 (95% CI, 5.48–82.40), respectively. Only HLA-DR15 and history of infectious mononucleosis interacted significantly on the additive scale (Synergy index, 3.78; p = 0.03). The five key risk factors jointly accounted for 63.8% (95% CI, 43.9–91.4) of FCD onset. High anti-EBNA IgG was another important contributor. Conclusions: A high proportion of FCD onset can be explained by the currently known risk factors, with HLA-DR15, ever smoking and low cumulative sun exposure explaining most. We identified a significant interaction between HLA-DR15 and history of IM in predicting an FCD of CNS demyelination, which together with previous observations suggests that this is a true interaction.